Profiling Users’ State of Mind towards Online Teaching and Learning in Higher Education - Tanipu, Zulkifli; Usu, Novi Rusnarty; Muhamad, Farid (English Department, Universitas Negeri Surabaya, 2022)
This study delves into the users’ state of mind with regard to the use of online platforms for educational purposes, specifically in the context of higher education. The purpose of this study, which employs a survey method, is to investigate how students perceive online teaching and learning in higher education and contribute to the growing collaboration between higher education researchers studying 21st-century learning concepts and Indonesian universities, which are increasingly implementing online teaching and learning. This study analyses various significant problems, including the process of online teaching and learning at universities, the difficulties of its implementation, and the users’ perceptions and attitudes towards the implementation of online teaching and learning. Overall, it is found that both students and lecturers prefer offline, face-to-face interaction in class rather than the online system. It is possible to state that both the lecturers and the students who have been attached to the conventional method of instruction and learning process are not prepared for the shift from offline to online learning. Even though online learning has been implemented, there is still a lack of consensus on the best practices for an effective online classroom. In addition to this, the fact that the institution does impose any fixed regulation also plays an important role in this. Keywords: State of Mind, Online Teaching and Learning, Higher Education